Simulation-Based Studies on FAGeI3-Based Lead (Pb2+)-Free Perovskite Solar Cells - Saood Ali; Khursheed Ahmad; Rais Ahmad Khan; Praveen Kumar (Crystals, 2025)
In the recent reports, it is clear that lead-free perovskite materials with low band gaps are desirable candidates for photovoltaic cells. In this regard, it was observed that germanium (Ge) is a less toxic lead-free metal that is significant for the preparation of Ge-based perovskite materials. Ge-based perovskite materials, for example, methyl ammonium germanium iodide (MAGeI3), cesium germanium iodide (CsGeI3), and/or formamidinium germanium iodide (FAGeI3) may be the suitable absorber materials and alternatives towards the fabrication of lead-free photovoltaic cells. In the past few years, few attempts were made to develop FAGeI3-based perovskite solar cells, but their photovoltaic performance is still under limitations. This is indicating that some significant and effective strategies should be designed and developed for the construction of Ge-based perovskite solar cells. It is believed that optimization of layer thickness, device structure, and selection of a suitable electron transport layer (ETL) may improve the photovoltaic performance of FAGeI3-based perovskite solar cells. Solar cell capacitance simulation, i.e., SCAPS is one of the promising software programs that can provide significant theoretical findings for the development of FAGeI3-based perovskite solar cells. The simulation studies via SCAPS may benefit researchers to save their energy and high cost for the optimization process in the laboratories. In this research article, SCAPS was adopted as a simulation tool for the theoretical investigations of FAGeI3-based perovskite solar cells. The simulation studies exhibited the excellent efficiency of 15.62% via SCAPS. This study proposed the optimized device structure of FTO/TiO2/FAGeI3/PTAA/Au with enhanced photovoltaic performance.